Globalization and management - Danimir Štros; Maja Coner; Daniel Bukovinski (Ekonomski Vjesnik, 2014)
Globalization as an ongoing process allows and promotes the development of economy of big countries as well as developing countries that are seeking their place in the global market. Interactive communication has been enabled between people, companies, civil society organizations and other institutions, whose needs can be met over the internet anywhere in the world and at any time. Also, professional and competent human resources are needed and therefore it is necessary to invest in new knowledge, innovation, new technologies and lifelong learning. In this environment, management sets its strategic goals through which it will be able to carry out the plans for the sale of products or services. Nowadays, a manager has to have interdisciplinary skills and lifelong education because only in this way it is possible to respond to the constant and rapid changes in the world. We are witnesses that Europe has reunited in order to compete with the less developed countries with their products and services. Europe has long refused to accept the managerial style of governance, particularly in public administration and is therefore far behind the U.S., but also the Third World countries. Until recently, European public administration was more focused on the implementation of laws and regulations and less on managerial governance of the U.S. type. Global environment requires the continuous research, monitoring competition, innovation and the ability to change rapidly.